An empirical study on the affecting factors of cloud-based ERP system adoption in Iraqi SMEs - Jilani, Mohammed Ghulam; Mohd Aboobaider, Burhanuddin; Dawood, Faten Abed Ali; Al-yousif, Shahad Nidhal; Alkhayyat, Ahmed; Ali, Mohammed Hasan; Malik, Rami Qays; Jaber, Mustafa Musa (Science and Information Organization, 2023)
This paper aims to investigate the main factors that have an impact on the adoption of cloud-based enterprise resource planning (ERP) among small- and medium-sized enterprises (SMEs) in the Republic of Iraq using TOE, DOI, and HOT-fit as a theoretical framework. Data was collected from 136 decision maker senior executives, and IT managers in SMEs in the Republic of Iraq. A web-based survey questionnaire was used for data collection processes. The research model and the derived hypotheses were tested using SPSS and SmartPLS. The findings indicate several specific factors have a significant effect on the adoption of cloud-based ERP. This conclusion can be utilized in enhancing the strategies for approaching cloud-based ERP by pinpointing the reasons why some SMEs choose to adopt this technology and success during the adoption phase, while others still do not go forward with the adoption. This study provides an overview and empirically shows the main determinants logistical factors that might face SMEs in the Republic of Iraq. The findings also help SMEs consider their information technologies investments when they think to adopt cloud-based ERP.